Desigualdades: reconocimiento de los cuidados y violencia contra las mujeres en contexto de Covid-19 - Bustillos-Chinchón, Diego (2020)
The COVID-19 pandemic has placed the health of humanity at the center of the global agenda. Likewise, by showing the structural situation of violence against women and diversity, it reflects the structural problems of human rights violations that we have as a society. In this sense, it has allowed us to see the area of ​​care as a central part of the economy, despite being classified as an invisible aspect. Today, when it has become more than evident that care jobs are life-preserving activities, it is necessary to discuss and rethink these jobs with the aim of subverting the power structures that run through them. In this essay, it is intended to show and raise awareness of the problem of how the health crisis affects gender relations and the sexual division of labor in our society, since the effects on women and diversities are devastating at the social political and economic level. Additionally, it seeks to deepen the dimensions and problems that concern women in this context. The purpose is to analyze and understand that this is a collective problem and that, as such, it requires collective responses. This implies transcending care as a family responsibility and recognizing it as a social responsibility managed by us and by the State as referents for construction in everyday life and in public policies. To achieve the objectives of this work, a literature review and analysis of the fundamental bibliography on studies on gender violence and care was carried out, in order to include a broad view with a multiple perspective towards its research.